Gender stereotypes in semantics of Spanish proverbs - Aleksandrovna, Tkachyova Anastasiya; Stanislavovna, Sharapova Lola; Abdusamiyevna, Vakhidova Anastasiya (Linguistics and Culture Review, 2021)
This article is dedicated to the investigation of gender stereotypes expressed in the Spanish language picture of the world on the material of Spanish proverbs about women and men. In the course of the investigation, we classified gender stereotypes to 6 types: age-related, descriptive, psychological, social, functional and sexual and gave examples for each type.